Pengaruh Penerapan Model Pembelajaran Inquiry Training Terhadap Keterampilan Proses Sains Siswa SMA - Devi, Icha Silviana; Sesunan, Feriansyah; Wahyudi, Ismu (Universitas Nurul Huda, 2019)
This research aimed to find out the influence of the implementation of the inquiry training learning model on the science process skills of high school students and to find out the science process skills of students applying the inquiry training learning model. The sample of this research were in class XI IPA 1 and XI IPA 4 at a senior high school in Gadingrejo, with a pretest-posttest control group with non equivalent research design. The data were tested by N-gain analysis, normality test, homogeneity test, and independent sample T-test. Based on the results of N-gain, science process skills in the experimental classes have an N-gain average value of 0.66 with the medium category. Whereas, in the control class the N-gain average value is 0.16 that is classified into low category. Test results for independent sample T-test Sig. (2-Tailed) is less than 0,05. It can be concluded that there is an effect of applying the inquiry training learning model on students' science process skills. Based on the results of observation, the science process skills of students in the class applying the inquiry training learning model had a very good classification of 23 students and a good classification of 6 students.